Board of Editor - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2021)
Paper Writting RegulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows.-          Papers must be a real work of the author.-          Papers has never been published in other media.-          Papers must contain discussion about Infrastructure & Facility Asset Management.-          Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM.-          The paper has to take references minimum 8 of references, which 3 of them are primary reference from Scientific Journal.-          Paper lengths are limited in 8-16 pages.-          Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifamScope of TopicJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited, of  the following.-          I & F Function-          I & F Demand - Supply-          I & F User Behavior-          I & F Policy-          I & F Planning-          I & F Administration Aspects-          I & F Operation System-          I & F Maintenance System-          I & F Evaluation Technique-          I & F Disposal-          I & F Economical Aspect-          I & F Financial Aspect-          I & F Management Organization-          I & F Spatial Aspects and Environmental AspectsReviewerFarida Rachmawati, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaMahendra A. Maulana,  Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaErli Martha, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaJanuarti Jaya Eka Putri, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaHitapriya Suprayitno, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaEko Budi Santoso, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaSatria Darmanegara, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaRia Asih Aryani Soemitro, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaDewa Made Frendika, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaAdji Pamungkas, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, IndonesiaAnastasia Caroline Sutandi, Universitas Parahyangan, Bandung